You are on page 1of 9

LECTURE NOTES FOR

MMAN 3200

MODULE A - LINEAR SYSTEMS ANALYSIS

These notes consist of Lectures 0 to 11 covering the syllabus taught in the


first 4.5 weeks of the term.
There may be minor differences of text and examples compared to what
is offered in the lectures.

1
LECTURE 0: LAPLACE TRANSFORMS – ASSUMED KNOWLEDGE

To create a LAPLACE TRANSFORM of f(t) we apply:


F(s) = L {f(t)} = 
0
e-st·f(t)dt

This way a new complex variable, s, is introduced, s = σ+ jω

Finding the inverse is normally achieved using tables and comparing the form of
G(s).Vi(s) with standard forms.

COMMON TRANSFORMS

Often useful when describing an input to a system

1. Unit Step:



L {u(t)} = 
0
e-st.1.dt = -e-st/s =1/s
0

2. Unit Impulse:

Let Δh Δt = 1 (for a unit impulse)

t
L {δ(t)} = 
0
e-st.Δh.dt

2
t
-st
= -Δh.e /s
0
= (-Δh /s)(e -sΔt
– 1)

Approximate

e-sΔt = 1 – sΔt + (sΔt)2/2! - … = -Δh/s (1 – sΔt – 1)

= ΔhΔt =1

3. Ramp of slope A:


 
L {At} = 
0
-st
e .At.dt = -At.e /s -st
-(- 
0
A.e-st/s.dt)
0
(remember partial integration: ∫ 𝑢𝑑𝑣 = 𝑢𝑣 − ∫ 𝑣𝑑𝑢)

= -A/s ( ∞ x 0 – 0 x 1 ) – A/s2 ( 0 – 1 )

= A/s2

4. Exponentials


L {Ae }-at
= 
0
e-st. Ae-at.dt


=A 
0
e-(a+s)tdt


-(a+s)t
= -[A/(s + a)] (e )
0

= A/(s + a)

3
5. Derivatives


L {f ′(t)} = 
0
e-st f ′(t).dt

 
-st
= e f(t) +s 
0
e-st f(t)dt
0

= - f(0) + s F(s) where f(0) is the function evaluated at


the point t=0
If the differential is more than first order, we can continue the process to get the
general result.

L {f n(t)} = sn F(s) – sn-1 f(0) – sn-2 f ′(0) - … - f (n-1)(0)

If all the initial conditions are zero i.e. f(0) = f ’(0) = … = 0 then taking the transform
of a differential equation is like multiplying by s instead of differentiating. E.g.

K θi (t) = A  0 (t) + B  0 (t) + C θ0 (t) becomes:

K θi(s) = (As2 + Bs + C) θ0(s)

6. Integrals

t
Suppose that g(t) = 
0
f(τ)dτ, so that g′(t) = f(t)

L {f(t)} = L { g  (t)} = sG(s) – g(0)

However from the definition of g(t) above, g(0) → 0

L {∫f(t).dt} = L {g(t)}

= G(s)

= 1/s L {g′(t)}

= 1/s L {f(t)}

= F(s)/s

This integration is equivalent to dividing by s.

4
7. The Initial Value Theorem.

We can find f(0) by using:

lim 𝑓(𝑡) = lim [𝑠𝐹(𝑠)] = 𝑓(0) , a limiting value at the beginning.


𝑡→𝑜 𝑠→∞

8. The Final Value Theorem.

We can find f(∞) by using:

lim 𝑓(𝑡) = lim[𝑠𝐹(𝑠)] = 𝑓(∞) , which is also called a steady state value.
𝑡→∞ 𝑠→0

7. & 8. Can be used as a partial check on whether you have transformed correctly e.g.

if f(t) = Ke-αt then F(s) = K/(s + α)

Thus
lim
t→0
f(t) = lim
s→∞
sK/(s + α) = lim K/(1 + α/s) =K QED
s →

lim f(t) = lim sK/( s + α) =0 QED


t→∞ s→0

LAPLACE SHIFT THEOREMS

Complex domain shift: if the function in the time domain contains an exponential, we
can simplify the transform by using:

L {e-at.f(t)} = F(s + a)

Similarly

L {e-bt.sinωt} = ω
(s + b)2 + ω2
Time domain shift: if the function in the complex domain contains an exponential, we
can simplify the inverse transform by using:

L -1{e-as.F(s)} = u(t – a) f(t – a)

5
This says that the Laplace transform can be found for a signal that does not start at t =
0. Remember u(t – a) is:
1

t
0 a

We can combine wave shapes to generate a composite shape.

This A y(t)
=

This A ramp function from t=0


+

This A negative ramp from B


+

This A negative step from B

B
The composite function in Laplace is:

L {A/Bt} – L {A/Bt} – L {A}


t = 0 to ∞ t = B to ∞ t = B to ∞

= A - e-Bs A - e-Bs A
Bs2 Bs2 s
𝐴
 L {y(t)} = 𝐵𝑠2 [1 - e-bs(1 + Bs)]

PARTIAL FRACTIONS

Once a function in the Laplace domain has been obtained, we need to consider
specifying it in its simplest form to aid inversion. Creating partial fractions usually
achieves this aim.

Note L {a f(t) + b g(t)} = a L {f(t)} + b L {g(t)}

In words this means that if the constituent parts of a system add together, we can
transform them independently. Similarly for the inverse transform. L is a linear
operator!

Any complex-domain function has the form N(s)/D(s) where D(s) has components
like (s + d1)(s + d2)(s2 + d3s + d4) etc. in which case the partial fraction expansion
would look like:

N(s) A B Cs + D
D(s) = (s + d1) + (s + d2) + s2 + d3s + d4

6
If the root is repeated n times, we must include the terms
A1 A2 An
2 +…+
(s + d1) + (s + d1) (s + d1)n

Examples:

1. Determine the Partial Fraction of F(s) = (s + 3)/(s2 + 3s + 2)

= (s + 3)/[(s + 2)(s + 1)]

 F(s) = A/(s + 2) + B/(s + 1)

 (s + 3)/ [(s + 2)(s + 1)] = [A(s + 1) + B(s + 2)] /[(s + 2)(s + 1)]

 (s + 3) = A(s + 1) + B(s + 2)
Now we can equate the coefficients with 𝑠1 or 𝑠 0 to obtain two equations and solve
them for A and B.

An alternative way:

s = -1  2=B

s = -2  1 = -A

 F(s) = 2/(s + 1) – 1/(s + 2)

 f(t) = (2e-t – e-2t) u(t)

2. Determine the Partial Fraction of F(s) = 2(s + 6)/[s(s + 2)(s + 4)]

𝐴 𝐵 𝐶 𝐴(𝑠+2)(𝑠+4)+𝐵𝑠(𝑠+4)+𝐶𝑠(𝑠+2)
𝐹(𝑠) = 𝑠 + 𝑠+2 + 𝑠+4 = 𝑠(𝑠+2)(𝑠+4)

Equate the numerators 2(s + 6) = A(s + 2)(s + 4) + Bs(s + 4) + Cs(s + 2)

For s=0 12 = 8A A = 1.5

s = -2 8 = -4B B = -2

s = -4 4 = 8C C = 0.5

F(s) = 1.5/s – 2/(s + 2) + 0.5/(s + 4)

Now find f(t).

7
3. If a function is given as: Y(s) = (2s2 + 6s + 6)/[(s + 2)2(s2 + 2s + 2)] find the
partial fraction expansion.

We must generate:

Y(s) = A/(s + 2) + B/(s + 2)2 + (Cs + D)/(s2 + 2s + 2)

2s2 + 6s + 6 = A(s + 2)(s2 + 2s + 2) + B(s2 + 2s + 2) + (Cs + D)(s + 2)2

Equate the coefficients:

of s3, 0=A+C
of s2, 2 = 2A + 2A + B + 4C + D
of s1, 6 = 2A + 4A + 2B + 4C + 4D
of s0, 6 = 4A + 2B + 4D

Four equations with four unknowns yields: A = 0, B = 1, C = 0, D = 1

Hence Y(s) = 1/(s + 2)2 + 1/(s2 + 2s + 2)

case 7 case 22

We can find the time domain equivalent

Y(s) = 1/(s + 2)2 + ½ 2/[s2 + 2 √2(1/√2) s + (√2)2]

y(t) = L -1{Y(s)} = (te-2t + e-tsint) u(t)

Solutions Using the Method of Residues

The residue Ri, the 𝑖 𝑡ℎ numerator of the partial fraction expansion of a function F(s) is
given by:

F(s).(s + ai) where –ai is the root of the denominator.


s = − ai

Example:

Say F(s) = 3s2 + 2s + 1


(s + 1)(s2 + 12s + 32)

= 3s2 + 2s + 1
(s + 1)(s + 4)(s + 8)
This will expand into:

F(s) = R1 R2 R3
+ +
(s + 1) (s + 4) (s + 8)
8
(3s2 + 2s + 1)(s + 1) 3–2+1 2
 R1 = = =
(s + 1)(s + 4)(s + 8) s = -1 3x7 21

(3s2 + 2s + 1) 48 – 8 + 1
 R2 = = = -41
(s + 1)(s + 8) s = -4 -3 x 4 12

(3s2 + 2s + 1) (3 x 64) – 16 + 1 177


 R3 = = =
(s + 1)(s + 4) s = -8 -7 x -4 28

2 41 177
 F(s) = - +
21(s + 1) 12(s + 4) 28(s + 8)

The Heaviside’s Expansion Theorem

To find L -1{P(s)/Q(s)} we use:

𝑛
𝑃(𝑠)
∑ | ∙ 𝑒 𝛼𝑖 𝑡
𝑄 ′ (𝑠)
𝑖=1 𝑠=𝛼𝑖

Example:
If F(s) = (s + 2) = P(s)
(s + 3)(s + 1) Q(s)
d
Q′(s) = (s2 + 4s + 3) = 2s + 4
ds

 L -1{F(s)} = s+2 .e-3t + s+2 .e-t = ½ e-3t + ½ e-t


2s + 4 s = -3 2s + 4 s = -1

Let’s confirm this result by using inverse tables. We find:

= (c – a).e – (c – b).e
-at -bt
L -1 s+c
(s + a)(s + b) b-a

With a = 3, b = 1, c = 2

f(t) = -1e-3t – 1e-t = (½ e-3t + ½ e-t) u(t) QED


-2

You might also like